EFISIENSI PENGGUNAAN DANA ALOKASI KHUSUS UNTUK PENDIDIKAN MENENGAH DI KABUPATEN WONOSOBO: PENDEKATAN DATA ENVELOPMENT ANALYSIS - Azalia Setya Andini; Yanuar Pribadi (Inovasi Pembangunan : Jurnal Kelitbangan, 2022)
Implementation of fiscal decentralization in Indonesia is formed in an intergovernmental transfer or Balance Fund. It aims to improve public services, including the quality of education. This study aims to analyze the role of the Balance Fund especially Special Allocation Fund on the efficiency of secondary education at the high school level in Wonosobo Regency using a Data Envelopment Analysis. DEA is a method to analyze the efficiency of several DMUs based on specified inputs and outputs. This research uses data from senior/vocational high schools which are got the Special Allocation Fund in Wonosobo Regency in 2020-2021. The results indicate that there are DMUs that are not efficient yet. The local government ought to develop a performance indicator and a reward and punishment mechanism to improve the efficiency of secondary education so that the utilization of the Special Allocation Fund in education at Wonosobo Regency can achieve the specified targets.